Recent expansion of the non-recombining sex-linked region on Silene latifolia sex chromosomes - Filatov, D (Wiley, 2022)
Evolution of a non-recombining sex-specific region on the Y(or W)-chromosome (NRY) is a key step in sex chromosome evolution, but how recombination suppression evolves is not well understood. Studies in many different organisms indicated that NRY evolution often involves several expansion steps. Why such NRY expansions occur remains unclear, though it is though that they are likely driven by sexually antagonistic selection. This paper describes a recent NRY expansion due to shift of the pseudoautosomal boundary on the sex chromosomes of a dioecious plant Silene latifolia. The shift resulted in inclusion of at least 16 pseudoautosomal genes into the NRY. This region is pseudoautosomal in closely related Silene dioica and Silene diclinis, indicating that the NRY expansion occurred in S. latifolia after it speciated from the other species ~120 thousand years ago. As S. latifolia and S. dioica actively hybridise across Europe, interspecific gene flow could blur the PAR boundary in these species. The pseudoautosomal genes have significantly elevated genetic diversity (π~3% at synonymous sites), which is consistent with balancing selection maintaining diversity in this region. The recent shift of the PAR boundary in S. latifolia offers an opportunity to study the process of on-going NRY expansion.